Evolución ecomorfológica de los tipos de enrollamiento en los trilobites durante el Paleozoico (2020)
Morphology allows to extract clear evidence in patterns of disparity in conjunction with characteristics of the habitat. In this work, comparisons between environmental patterns and taxonomic characters are evidenced in conjunction with the morphological disparity in trilobites over time. The morphological evolution concerning the enrollment and the influence of the habitat for the different specimens in the Paleozoic are mainly evaluated. The morphological disparity is conceived from the concept of geometrics morphometry, to achieve more precise ecomorphological patterns. Likewise, these analyzes are carried out based on data set made up of approximately 340 species, including samples from all orders of trilobites and periods present during the Paleozoic Era. Finally, the results expose patterns of diversity related to the habitat, as well as in the different enrollment types with evident preferences for taxa over time.